2013
DOI: 10.1109/tit.2012.2214203
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of the Algebraic Degree of $F^{-1}$ on the Algebraic Degree of $G \circ F$

Abstract: We present a study on the algebraic degree of iterated permutations seen as multivariate polynomials. The main result shows that this degree depends on the algebraic degree of the inverse of the permutation which is iterated. This result is also extended to noninjective balanced vectorial functions where the relevant quantity is the minimal degree of the inverse of a permutation expanding the function. This property has consequences in symmetric cryptography since several attacks or distinguishers exploit a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…The degree of such a permutation F is the algebraic degree of the (n, n) vectorial Boolean function [5] or also called n-bit S-box. Any such function F (x) can be considered as an n-tuple of Boolean functions (f 1 (x), .…”
Section: Preliminariesmentioning
confidence: 99%
“…The degree of such a permutation F is the algebraic degree of the (n, n) vectorial Boolean function [5] or also called n-bit S-box. Any such function F (x) can be considered as an n-tuple of Boolean functions (f 1 (x), .…”
Section: Preliminariesmentioning
confidence: 99%
“…Research by Boura and Canteaut on the algebraic degree of iterated permutations seen as multivariate polynomials shows that the degree depends on the algebraic degree of the inverse of the permutation which is iterated [5]. This indicates exceptional algebraic security for our proposal.…”
Section: Observationmentioning
confidence: 92%
“…This is a desirable quality in a Sponge-based cryptoprimitive as computation of inverse is not required in normal operation. Boura and Canteaut have showed that complex inverse makes the resulting iteration strong even if it is not explicitly computed [5]. We have discovered new functions of φ type which exhibit much more radical asymmetry than the χ function of KECCAK.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations